Projeto e validação de uma caixa de solo para ensaios da interação dinâmica máquina solo - Ferreira, Tomás de Aquino (2010)
The soil bins became an important tool in research centers to study the dynamic interaction soil machine. The objective was to design, build and evaluate the operational performance of a soil bin, consisting of power and displacement systems; system of soil preparation and measurement system, needed to conduct research regarding the dynamics of soil machine interaction. The construction of the soil bin was conducted in the Department of Engineering Federal University (UFLA) in Lavras, MG. For its evaluation, tests were conducted operational performed the car dynamometer, the tools of tillage and plow into a different speed conditions in advance. Measured are speed, power and parameters that characterize the physical and mechanical property of soil under study. The results allowed the conclusion that the car dynamometer allows the simulation of field operations with agricultural equipment efficiently.